Research progress of Chinese medicinal monomers in the process of melanoma occurrence - Yan Shang; Hailong Zhao (Pharmaceutical Biology)
Context Melanoma’s aggressiveness and resistance to radiotherapy highlight an urgent need for innovative treatments. Traditional Chinese medicine (TCM) offers a unique approach through its ‘four natures’ theory—cold, cool, warm, and hot.Objective This review aims to explore the potential of TCM’s ‘four natures’ herbal monomers in melanoma treatment, providing an alternative to conventional therapies.Materials & methods A systematic literature review was conducted by accessing various databases, including Baidu Scholar, PubMed, Science Citation Index Expanded (SCIE), and China National Knowledge Infrastructure (CNKI), to synthesize the most recent findings on traditional Chinese medicine monomers. Furthermore, this review elucidated the mechanisms underlying their role in melanoma retention.Results TCM’s multi-component, multi-target approach has shown promise in addressing melanoma’s complexity, with specific monomers demonstrating the ability to modulate tumor behavior.Discussion and Conclusions The ‘four natures’ theory in TCM presents a novel perspective for melanoma treatment, warranting further investigation into its clinical applications and potential integration with modern oncology.